Ocorrência de infecção nosocomial por Candida spp. no Hospital Universitário Cassiano Antonio de Moraes (HUCAM) e avaliação da anfotericina B e voriconazol na inibição de formação de biofilme pelas espécies isoladas - Ribeiro, Aline Dias (2013)
INTRODUCTION: Bloodstream fungi infections have highlighted mainly by the growing number of cases of candidemia (infections by Candida spp this site). Currently, this fungus figure as one of seven most common pathogens in nosocomial infections, presenting mortality rates gross between 40 and 70%, and attributed of 50%. Biofilm formation is often associated with the persistent Candida spp. infection and it complicates the treatment due to high resistence that fungal cells acquire to antifungal drugs, in these circumstances. OBJECTIVES: Estabilish the candidemias incidence in University Hospital Cassiano Antônio de Moraes (HUCAM), between 1 º of March 2011 to December 30 2012; estabilish prevalence rates of Candida spp. species e test the potential drug activity of amphotericin B and voriconazole in the inhibition of biofilm formation by the species isolated. MATERIALS AND METHODS: Information on the total number of admissions and patient-days in the ICU and NICU s HUCAM were provided by statistics sector and 32 Candida spp. strains obtained from blood, urine and catheter tip were isolated in Laboratory of Clinical Analysis of the hospital. Inhibition of biofilm formation tests were analized using statistical of Wilcoxon, of Signs and of Mann-Whitney. RESULTS: HUCAM s sector with greater incidence of candidemia was the NICU (8.6 / 10,000 patients-day and 14,2 / 1,000 hospitalizations). Candida spp was the fifth most isolated microorganism of BSI, with predominance of non-albicans species (81%), being C. parapsilosis the species most frequent. In NICU, the frequency of candidemia by C. albicans was 67% and the only non-albicans specie isolated was Candida parapsilosis. In the evaluation of biofilm formation inhibition was evidenced that the concentrations of amphotericin B statistically significant were: 128 μg / mL for the species C. albicans studied, C. parapsilosis and C. tropicalis and 64 μg / mL for the species grouped into "others". Voriconazole was able to inhibit biofilm formation only for isolates of the species C. albicans and at the highest concentration tested (64 μg / ml). CONCLUSIONS: The highest incidence of candidemia in HUCAM was found for neonates interned in NICU. The distribution of Candida species ranged according with sectors the hospital, but suffered little alteration in relation to period studied. Overall, amphotericin B was more effective than voriconazole in the inhibition of biofilm formation by Candida species